2012
DOI: 10.7314/apjcp.2012.13.6.2879
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Premenopausal Breast Cancer: A Case-control Study in Uruguay

Abstract: In order to thoroughly analyze risk factors of breast cancer (BC) in premenopausal Uruguayan women, a case-control study was carried out at the Pereira Rossell Women's Hospital, Montevideo, where 253 incident BC cases and 497 frequency-matched healthy controls were interviewed on menstrual and reproductive story, were administered a short food frequency questionnaire and undertook a series of body measurements necessary to calculate body composition and somatotype. Odds ratio (OR) coefficients were taken as es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 31 publications
2
27
2
2
Order By: Relevance
“…In line with the studies by Naini et al in Mazandaran province, Iran (Naieni et al, 2007) and Yavari et al in Tehran (Yavari et al, 2004), the results of bivariate analysis showed that postmenopausal status increased the risk of breast cancer, but this effect diminished in multivariate analysis after adjusting for age, which is also in agreement with the results of other studies conducted on the issue (Ghiasvand et al, 2011). Similar to other studies (Yavari et al, 2004;Ghiasvand et al, 2011;Ghiasvand et al, 2012;Ronco et al, 2012a), the present study revealed no significant association between breastfeeding and risk of breast cancer (Yavari et al, 2004;Naieni et al, 2007;Gajalakshmi et al, 2009). Although childbearing could reduce the risk of breast cancer, the role of breastfeeding is not clear yet (do Carmo Franca-Botelho et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…In line with the studies by Naini et al in Mazandaran province, Iran (Naieni et al, 2007) and Yavari et al in Tehran (Yavari et al, 2004), the results of bivariate analysis showed that postmenopausal status increased the risk of breast cancer, but this effect diminished in multivariate analysis after adjusting for age, which is also in agreement with the results of other studies conducted on the issue (Ghiasvand et al, 2011). Similar to other studies (Yavari et al, 2004;Ghiasvand et al, 2011;Ghiasvand et al, 2012;Ronco et al, 2012a), the present study revealed no significant association between breastfeeding and risk of breast cancer (Yavari et al, 2004;Naieni et al, 2007;Gajalakshmi et al, 2009). Although childbearing could reduce the risk of breast cancer, the role of breastfeeding is not clear yet (do Carmo Franca-Botelho et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, a case-control study in Malaysia (382 breast cancer cases and 382 control group) carried out by Sulaiman et al (2011) reported a lack of association between total fat and fat subtypes intake and BC risk in premenopausal and postmenopausal women. On the other hand, Ronco et al (2012) observed an increased risk with a high consumption of red meat and fried food (OR=2.20, 95%CI=1.35-3.60 and OR=1.79, 95%CI=1.12-2.84, respectively) in premenopausal Uruguayan women. Contrary to these observation, a high intake of plant food exhibited a protective effect (OR=0.41, 95%CI=0.25-0.65).…”
Section: Dietmentioning
confidence: 90%
“…The mechanism of breast carcinogenesis is still not fully understood. Breast cancer may result from multiple environmental, dietary, hereditary, racial and socioeconomic risk factors (Ronco et al, 2012a;Ronco et al, 2012b;Zhang et al, 2012;Zhou et al, 2012a;Zhou et al, 2012b;Shamsi et al, 2013;Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%